Young gay men's sexism predict their male facial masculinity preference in China. (April 2015) - Zheng, Lijun; Zheng, Yong
Highlights: The relationship of sexism and facial masculinity preference was examined in gay men. Hostile sexism was positively correlated with facial masculinity preference. Protective paternalism was negatively correlated with facial masculinity preference. Abstract: Previous studies have indicated that sexism is related to romantic partner preference in heterosexual men and women. We examined the association between sexism and preference for male facial masculinity among 185 gay men in China. Hostile sexism (HS; hostility toward women who oppose traditional roles) was positively correlated with facial masculinity preference. Protective paternalism, a component of benevolent sexism (BS; ideation of women who conform to traditional gender roles) was negatively correlated with facial masculinity preference. These findings indicated that sexism was related to male facial masculinity preferences in gay men. Thus, regardless of sexual orientation, men high on HS tend to prefer sex-typicality in potential partners.